Manipulation of sensitivity of the surface plasmon polariton waves at the interface of high magneto-optical medium and silver metal using angular interrogation - Qaisar Khan; Bakht Amin Bacha; Iftikhar Ahmad; Majid Khan; Ali Akgul; Sayed M. EI Din; Amir Khesro (Results in Physics, 2023)
In this manuscript, sensitivity of the surface plasmon polariton waves (SPPs) using angular interrogation is coherently manipulated at the interface of four level high magneto-optical medium and silver metal using prism geometry. The control and probe fields detuning, Rabi frequency and decay rate manipulated significantly the angular interrogation of sensitivity of the surface plasmon polariton waves. The permittivity ϵd and permeability μd of the high magneto-optical medium play an important role in the manipulation of the sensitivity. The sensitivity is a function of control field detuning. The maximum sensitivity is reported to 800 deg/RIU with control field detuning. The minimum sensitivity is investigated to 6 deg/RIU with probe field detuning and Rabi frequency of control field. The reported results have useful applications in data storage and chemical sensing technologies.